Elucidation of interleukin-17A in regulating osteogenic differentiation of stem cells from human exfoliated deciduous teeth - Sebastian, Alphy Alphonsa (2018)
To date, limited studies describe the involvement of interleukin-17A(IL-17A) in bone remodelling. Receptor activator of NF-κB ligand (RANKL) has been shown to augment bone resorption whereas osteoprotegerin (OPG) favours osteogenesis. Hence, the aim of the present study was to determine the potential role of IL-17A in osteogenic differentiation and regulation of OPG/RANKL system of the stem cells extracted from human exfoliated deciduous teeth (SHED). SHED were cultured in 2 different conditions; one in complete alpha minimum essential medium (-MEM) and the other in complete -MEM medium supplemented with osteogenic medium (OM). Both groups were treated with various concentrations of rIL-17A i.e. 5, 10, 25, 50 and 100ng/ml respectively. Treated cells were then analyzed for proliferative activity by MTS assay, differentiation by alkaline phosphatase assay, mineralization activity by Alizarin red and Von Kossa stainings, expressions of bone and stem cell markers and apoptosis by flow cytometry analysis. Osteogenic differentiation potential of SHED was further evaluated by measuring the expressions of selected osteogenic markers i.e. ALP, COL1A1, RUNX2, OCN, OPN, OPG and RANKL by quantitative PCR and Western blot. The involvement of MAP kinase (MAPK) signalling pathway and miRNA-145 in the osteogenic differentiation mechanism of rIL-17A-treated SHED were also evaluated in the study. Treatment of rIL-17A on SHED and SHED + OM demonstrated increased proliferation and ALP activities in a dose-dependent manner. Similarly, stainings by Alizarin red and VonKossa indicated increased mineralization activity by rIL-17A-treated SHED and SHED + OM. Interestingly, treatments of cells with rIL-17A showed gradual declining of stem cells markers (c-Myc and Nanog) in both groups while increased expression of osteogenic markers (ALP and COL1A1) was evident as the days progressed. SHED-treated with rIL-17A also inhibited apoptosis in both groups. Moreover, the expressions of ALP, COL1A1, RUNX2, OCN, OPN and OPG were significantly up-regulated in rIL-17A-treated SHED in both groups. However, the RANKL expression was downregulated. Interestingly, the OPG/RANKL ratio was significantly enhanced in rIL-17A-treated groups. We also demonstrated that IL-17A activated MAPK signalling pathway by significant upregulation of all upstream activators and downstream targets of ERK, p38 and JNK pathway. In addition, rIL- 17A-SHED also showed increased expression of miR-145. These findings demonstrated for the first time that IL-17A promotes proliferation, enhances osteogenesis by promoting osteogenic differentiation through the alteration of OPG/RANKL signalling pathway and increases mineralization activity. We also demonstrated possible roles of MAPK signalling pathway and miR-145 in osteogenic differerentiation of SHED induced by IL-17A. These findings suggest the pivotal role played by IL-17A in bone remodelling mechanism.